Phytochemical Study and Antioxidant Activity of Anti-Aging Cream from Three Rote Plants - Muntasir Muntasir; Cahyani Purnasari; Nurul Fatmawati Pua Upa (Journal of Innovative and Creativity, 2025)
This study examines the antioxidant potential of three plants used by the people of Rote Ndao in skin care, namely Puteh Wood (Alstonia scholaris), Kesambi (Schleichera oleosa), and Moringa (Moringa oleifera). The background of the study was based on skin aging triggered by oxidative stress due to free radicals. The research objectives were to identify active phytochemical compounds, formulate the three extracts into creams, and analyze their potential synergism and antioxidant activity in a descriptive-exploratory manner. Extraction using 70% ethanol was carried out by maceration method, while phytochemical identification was applied by color reaction and precipitation tests for alkaloids, flavonoids, tannins, saponins, terpenoids, and steroids. Vanishing cream-based cream formulation was successfully made with good physical characteristics, namely homogeneous, pH 6.8, and spreadability of 5.7 cm. Qualitative antioxidant activity test using DPPH method showed a rapid change of DPPH purple color to pale yellow in mixed extracts and creams, indicating stronger antioxidant activity than single extracts. The results indicate the presence of potential antioxidant compounds in all three plants and an indication of synergistic effects between extracts that may come from the interaction of different classes of phytochemical compounds. These findings provide an important basis for more in-depth quantitative studies in the development of natural ingredient-based antioxidant products. Keywords: Anti-aging, Phytochemical, Cream, Polyherbal, Synergism, Qualitative, Rote Ndao, DPHH